Increased efficiency of finite element slope stability analysis by critical failure path detection - Farnsworth R.; Arora A.; Griffiths D.V. (My University, 2025)
A new and efficient method of factor of safety determination has been developed, wherein after a small number of iterations, and for a given strength reduction factor which is typically higher than the true factor of safety, the software will look for a critical failure path through the slope. If found, the software then determines that the slope has failed and no additional iterations are needed. By doing this, most iterations in the non-convergent range are eliminated. The paper describes an algorithm that searches for a continuous path of Gauss points across the slope that have failed and are deforming plastically. The avoidance of unnecessary iterations, leads to significant computational savings. © 2018 Taylor & Francis Group, London, UK.